Answer:
Step-by-step explanation:
In the given sequence, the terms are increasing in arithmetic progression. The common difference, d between successive terms is 2
The formula for determining the nth term of an arithmetic sequence is expressed as
Tn = a + (n - 1)d
Where
a represents the first term of the sequence.
d represents the common difference.
n represents the number of terms in the sequence.
From the information given,
a = 1
d = 2
Therefore, the expression for the general term for the sequence is
Tn = 1 + 2(n - 1)
Answer:
x is equal to 6
Step-by-step explanation:
4x=24
divide both sides by 4
4 eliminates 4 leaving x behind
4 divides 24 making x =6
It is C: Given, Reflexive Property
Answer:
ok
Step-by-step explanation: